We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
104
1
avatar

What are the first and second derivatives of the function f(x)=3x/2x^2-18

 Nov 25, 2018
 #1
avatar+99415 
+1

I assume this is

 

3x /   [ 2x^2 - 18 ]        if so, we can wrtite this as

 

(3x) ( 2x^2 - 18)^(-1)

 

First derivative

 

3 ( 2x^2 - 18)^(-1)  - 3x (2x^2 - 18)^(-2) (4x) =

 

3( 2x^2 - 18 )^(-1) - 12x^2 (2x^2 - 18)^(-2)   =

 

3 ( 2x^2 - 18)^(-2)    [ (2x^2 - 18 - 4x^2 ] =

 

3 (2x^2 - 18)^(-2) [ -2x^2 - 18 ] =

 

3 ( 2x^2 - 18)^(-2) [ -2 (x^2 + 9 ] =

 

-6 (x^2 + 9) (2x^2 - 18)^(-2)

 

Second derivative

 

- 6  [   2x (2x^2 - 18)^(-2)  - 2 (x^2 + 9) (2x^2 - 18)^(-3) (4x) ]   =

 

-6 [  2x (2x^2 - 18)^(-2)   - 8x (x^2 + 9) (2x^2 - 18)^(-3) ]  =

 

-6 [ 2x (2x^2 - 18)^(-3)  ] [   (2x^2 - 18) - 4( x^2 + 9) ]   =

 

-6 [ 2x (2x^2 - 18)^(-3) ]   [ 2x^2 - 18 - 4x^2 - 36 ]   =

 

-6 [ 2x (2x^2 - 18)^(-3) [ -2x^2 - 54 ]   =

 

6 [ 2x (2x^2 - 18)^(-3) (2)(x^2 + 27) ]  =

 

12 [ 2x (2x^2 - 18 )^(-3) (x^2 + 27)   =

 

24x (x^2 + 27) / [ (2^3 (x^2 - 9)^(-3) ] =

 

24x  (x^2 + 27) / [ 8 ( x^2 - 9)^(-3) ] \

 

3x (x^2 + 27) (x^2 - 9 )^(-3)

 

 

cool cool cool

 Nov 25, 2018

14 Online Users

avatar
avatar
avatar